An 8-year-old boy with diffuse cystic pulmonary tuberculosis: An intriguing story (Indian Journal of Case Reports, 2024)
Diffuse cystic lung disease due to pulmonary tuberculosis (TB) is rare. We describe an 8-year-old boy who presented with acute onset respiratory distress while on a compliant anti-tubercular treatment for a recently diagnosed pulmonary TB. On clinical examination, hypoxemia, clubbing, and features of the right-sided heart failure were observed. High-resolution computed tomography of the chest revealed extensive cystic lung parenchymal changes with ground glassing and consolidation, and echocardiography indicated the presence of pulmonary arterial hypertension. His treatment included supplemental oxygen, sildenafil, prednisolone, and anti-tubercular drugs. At the two-year follow-up, the patient showed complete clinical recovery and resolution of cysts on the chest X-ray.